Teaching Note—Teaching Student Interviewing Competencies Through Second Life. (2nd January 2017) - Tandy, Cynthia; Vernon, Robert; Lynch, Darlene
ABSTRACT: A prototype standardized client was created and programmed to respond to students in the 3D virtual world of Second Life. This automaton, called a chatbot, was repeatedly interviewed by beginning MSW students in a practice course as a learning exercise. Initial results were positive and suggest the use of simulated clients in virtual worlds as learning objects is worth further development and evaluation.